2017
DOI: 10.11604/pamj.2017.28.213.11007
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of neurosarcoidosis with progressive hearing loss

Abstract: Sarcoidosis is a granulomatous disease of unknown etiology that can involve several organ system. Neurological manifestations are not common and mostly include cranial neuropathies. However, auricular disorders are rare and exceptionally inaugural. We describe the case of a 46-year-old lady presented with hearing loss as the initial manifestation of sarcoidosis, and aim to raise awareness of this condition, that is often associated with significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A cochlear involvement either isolated or associated with the neuropathy cannot be entirely ruled out as suggested by images of cochlear enhancement on MRI in patient 1 and of labyrinthitis ossificans reported in the literature [Dhanjal et al, 2014;Greene et al, 2017]. Normal morphology and latencies of ABR reported in 1 patient with moderate bilateral hearing loss also suggest possible cochlear involvement [Taous et al, 2017].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A cochlear involvement either isolated or associated with the neuropathy cannot be entirely ruled out as suggested by images of cochlear enhancement on MRI in patient 1 and of labyrinthitis ossificans reported in the literature [Dhanjal et al, 2014;Greene et al, 2017]. Normal morphology and latencies of ABR reported in 1 patient with moderate bilateral hearing loss also suggest possible cochlear involvement [Taous et al, 2017].…”
Section: Discussionmentioning
confidence: 90%
“…In a review of the literature, Colvin [2006] reported 50 cases. Since then, fewer than 30 adult and pediatric cases have been referenced in PubMed [Colvin, Color version available online DOI: 10.1159/000514479 2006; Agari et al, 2007;Cama et al, 2011;Loor et al, 2012;Szmulewicz, and Waterston, 2012;Dhanjal et al, 2014;Rose et al, 2014;Jardine et al, 2015;Shimizu et al, 2016;Greene et al, 2017;Svrakic et al, 2017;Taous et al, 2017]. In most cases, hearing loss was mild to moderate and reversible after corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation